Air quality control handbook (McGraw-Hill, 1998)
This practical design-oriented handbook features unrivaled coverage of the provisions and implications of the 1990 Clean Air Act Amendments (CAA), and is the only resource to provide you with a balanced account of the regulatory, technical, and management aspects of air quality control. It examines the origins and effects of air pollution and the history of air quality control management before giving you crucial guidance on how to: comply more easily with the CAAA, including MACT standards, mandates on acid rain and ozone-destructive chemicals, and applications and reporting requirements; establish a solid air management policy that's linked to effective air quality control methods and activities, perform ambient air, continuous air, and stack monitoring as well as various forms of pollution testing,..